Pengembangan Media Pembelajaran Tata ara Dan Bacaan Shalat Fardhu Untuk Siswa Tunarungu Berbasis Android (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2020)
Abstract This research aims to develop learning media for children with special needs. This research uses research and development methods. The products that have been developed are then tested by material experts and media experts for feasibility testing. The result of the development process carried out is that the media used is included in the very decent category. The conclusions from the results of research and development of an android-based learning media program on Procedures and reading of Fardhu Prayers for deaf students are as follows: The product developed is a software application based on learning media android material Procedures and readings which include identity pages, menus, instructions, competencies, materials, evaluations, games and developer profiles. Based on assessments by media experts, material experts, beta test respondents and product validation test respondents. The resulting learning media is considered very suitable for use as a learning aidKeywords: deaf media, prayer procedures and readings Abstrak             Penelitian ini bertujuan untuk megembangkan media pembelajaran untuk anak berkebutuhan khusus penelitian ini menggunakan metode riset dan pengembangan. Produk yang telah dikembangkan kemudian diuji oleh ahli materi dan ahli media untuk uji kelayakan. Hasil dari proses pengembangan yang dilakukan adalah media yang digunakan termasuk dalam kategori sangat layak.. Simpulan hasil penelitian dan pengembangan program media pembelajaran berbasis android materi Tatacara dan bacaan Shalat Fardhu untuk siswa siswa tunarungu adalah sebagai berikut: Produk yang dikembangkan adalah aplikasi software media pembelajaran berbaasis android materi Tatacara dan bacaan yang mencakup halaman identitas, menu, petunjuk, kompetensi, materi, evaluasi, games dan profil pengembang. Berdasarkan penilaian ahli media, ahli materi, responden uji beta dan responden uji validasi produk. Media pembelajaran yang dihasilkan dinilai sangat layak digunakan sebagai salah satu alat bantu pembelajaran kata kunci: media tuna rungu, tata cara dan bacaan shalat